Semen quality in adult male survivors 5 years after the 2008 Wenchuan earthquake. (2nd May 2016) - Chen, X. M.; Chen, S. M.; Yue, H. X.; Lin, L.; Wu, Y. B.; Liu, B.; Jiang, M.; Ma, Y. X.
Summary: The influence of the Wenchuan earthquake on semen quality of adult male survivors is unclear. We investigated the semen quality included 673 male survivors from the worse‐affected counties in the earthquake between Aug 2008 and July 2013. Semen parameters including pH, volume, concentration, motility and morphology were measured according to the World Health Organization (WHO) criteria. Kruskal–Wallis analysis of variance was used to examine the statistical differences between years, and a logistic regression was used to analyse the impacts caused by earthquake on the changes of semen quality. We found the medians (5th and 95th) were 2.5 ml (0.6–5.5) for semen volume, 59.0 × 10 6  ml −1 [(13.0–133.0)] × 10 6  ml −1 for semen concentration, 46% (13–64%) for sperm progressive motility and 3.0% (0–17.5%) for normal morphology for adult male survivors. Semen concentration, the percentage of sperm progressive motility, total motility and sperm normal morphology were all decreased in the first 3 years, and the differences among years 1, 2 and 3 were significant except the percentage of sperm progressive motility ( P  <   0.05). The casualties and heavy housing damage caused by earthquake had a negative effect on semen quality. The main findings will provide further diagnosis and therapy basis of male fertility by data, for affected populations in the earthquake.